Gene Expression Variations of Red—White Skin Coloration in Common Carp (Cyprinus carpio) - Xiao-Min Li (International Journal of Molecular Sciences, 2015)
Teleosts have more types of chromatophores than other vertebrates and the genetic basis for pigmentation is highly conserved among vertebrates. Therefore, teleosts are important models to study the mechanism of pigmentation. Although functional genes and genetic variations of pigmentation have been studied, the mechanisms of different skin coloration remains poorly understood. The koi strain of common carp has various colors and patterns, making it a good model for studying the genetic basis of pigmentation. We performed RNA-sequencing for red skin and white skin and identified 62 differentially expressed genes (DEGs). Most of them were validated with RT-qPCR. The up-regulated DEGs in red skin were enriched in Kupffer’s vesicle development while the up-regulated DEGs in white skin were involved in cytoskeletal protein binding, sarcomere organization and glycogen phosphorylase activity. The distinct enriched activity might be associated with different structures and functions in erythrophores and iridophores. The DNA methylation levels of two selected DEGs inversely correlated with gene expression, indicating the participation of DNA methylation in the coloration. This expression characterization of red—white skin along with the accompanying transcriptome-wide expression data will be a useful resource for further studies of pigment cell biology.